Spiritual leadership and employee CSR participation: a probe from a sensemaking perspective - Zou, Wenchi (Journal of business ethics, 2023)
This study via the sensemaking perspective examines whether spiritual leadership can influence employee workplace spirituality and employee corporate social responsibility (CSR) participation. We also examine the joint effects of spiritual leadership and employee Machiavellianism on employee workplace spirituality. Using a sample of 556 employees from four commercial banks in China, analyses demonstrate that employee workplace spirituality mediates the relationship between spiritual leadership and employee CSR participation and that the indirect effect of spiritual leadership on employee CSR participation is dependent on the level of employee Machiavellianism. These results shed light on how and why spiritual leadership and employee Machiavellianism influence employee workplace spirituality and employee CSR participation. The theoretical and practical implications of these finding are discussed along with directions for future research.